Visual perception of the arm manipulates the experienced pleasantness of touch. (February 2019) - Keizer, Anouk; de Jong, Jutta R.; Bartlema, Lianne; Dijkerman, Chris
Abstract: Touch, such as a caress, can be interpreted as very pleasant. The emotional valence assigned to touch is likely related to certain bottom-up factors, such as optimal activation of C-tactile (CT) afferents. It is however unclear if besides somatosensory input, contextual factors related to the own body also play a role in the perceived pleasantness of touch. To test this, we manipulated visual appearance of the participant's arm (veridical vision, no vision, pixelated moving statistic projected onto the arm (i.e. crawling skin)). We used slow velocity stroking (CT optimal stroking) with a soft brush to induce pleasant touch, and fast velocity stroking as a control condition. After each visual condition we asked participants (N = 23) to rate the emotional valence of the stroking they felt. After slow velocity stroking ratings on perceived pleasantness (but not on perceived unpleasantness) were modulated by visual condition, with veridical vision of the arm resulting in higher pleasantness ratings than both no vision and pixelated vision. We conclude that contextual processes affect the perceived pleasantness of touch. These findings shed a new light on the underlying mechanisms of how humans experience pleasant touch and show that pleasant touch not solely dependents on bottom up information.